Association Between Cerebral Microbleeds and Depression in the General Elderly Population: A Meta-Analysis - Wang, Ruiming; Liu, Keqin; Ye, Xiaoyun; Yan, Shenqiang (Frontiers in Psychiatry, 2018)
Background: It remains unclear whether cerebral microbleeds (CMBs) are associated with depression in the general elderly population. We thus performed a meta-analysis to evaluate the relationship between depression and CMBs. Methods: A systematic literature search was conducted in EBSCO, PubMed and Web of Science for relevant studies that assessed the relationship between depression and the prevalence of CMBs. Results: Five eligible studies including 7328 patients were pooled in meta-analysis. The prevalence of CMBs was 18.0%. The prevalence of depression was 11.1%. The pooled analysis demonstrated odds ratio for CMBs and depression to be 1.187 (95% CI 1.005 to 1.403; p = 0.043) with no evidence of statistical heterogeneity (I2 = 0.0%, p = 0.621). Conclusions: Our meta-analysis of available published data indicated an increased prevalence of depression in the subjects with pre-existing CMBs. This finding supports the vascular depression hypothesis. Further studies are needed to investigate the role of CMBs in the pathogenesis and progression of depression, which might provide a potential target for the prevention and treatment.